The Role of Kyai Leadership in Enhancing Religious Values Among Millennials - Maula, Inayatul; Rofiki, Moh (Journal of Educational Management Research, 2025)
This study explores the role of Kiai in shaping the religious and social behaviors of the millennial generation within the community. As religious leaders adapt to modern challenges, the millennial generation’s engagement with spirituality has evolved, requiring innovative approaches in religious leadership. The research aims to investigate how Kiai leadership fosters religious devotion, social responsibility, and unity among his followers. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that Kiai serves as an exemplary figure (uswah hasanah), whose personal devotion and humility positively influence the members' religious practices and behaviors. His role as a socio-religious advisor has helped balance personal piety with social engagement, encouraging members to actively participate in charitable activities. Additionally, Kiai acts as a unifier of the community, fostering solidarity and inclusivity among members from diverse backgrounds. This research contributes to the understanding of contemporary Islamic leadership by demonstrating how Kiai multifaceted approach creates a transformative impact on millennial followers. It also recommends further research into similar non-formal religious communities to explore broader trends in modern Islamic leadership.